NALAR PERUMUSAN HUKUM BAGI KORUPTOR DI INDONESIA PERSPEKTIF HUKUM ISLAM - Triyanto, Andi (Varia Justicia, 2015)
Formulating the law of a case in the Islamic perspective must be supported on acomplete understanding of the problem being studied and appropriate legal basis of theQuran and Sunnah, so that the resulting legal products benefit the world and thehereafter. This paper studies how to formulate the law raised the case of corruption inIndonesia. Corruption was chosen for being a latent danger and enemy with allreligions and nations of the world, including Indonesia. The negative impact ofcorruption does not only count the number of the nominal rate but also the socialimpacts that can not be counted. Unravel corruption in Indonesia which has beenwidespread become urgent and important to find the best solution eradication. The factthat Indonesia is a unitary state which based on Bhineka Tunggal Ika, the law requiresthe formulation of corruption cases using a comprehensive approach to obtainappropriate legal products. The author uses the approach of sociology, anthropology,religion, geography, and economics (SAAGE). The approach is based on the need tostrengthen synergies source which is base on âunity on diversityâ law that has becomethe foundation of the state, for Islam as the religion of the majority of this is expected tobe the direction and strategy of the renewal application of Islamic law in Indonesia